LO052: Sticks and stones may break your bones, but does having a car crash in a rural location affect your access to EMS care and surgical intervention? The initial analysis of a unique EMS and Trauma Dataset. (2nd June 2016) - Kenney, M.B.; French, J.; Fraser, J.; Phelan, B.; Watson, I.; Benjamin, S.; Chisholm, A.; Pishe, T.; Middleton, J.; Atkinson, P.R.
Abstract : Introduction: In Canada, major trauma is a healthcare priority and in 2014 was responsible for over 15866 deaths, with a total economic burden of 26.8 billion dollars. Numerous factors influence the likelihood of occurrence and outcome from major trauma, including incident factors, host, EMS response, emergency, surgical and critical care. Traditionally trauma registers contained information that mainly concerning hospital treatment and host factors. This collaborative analysis uses matched data from a Provincial Trauma Research Register and records from a Provincial Ambulance Service.Methods: A retrospective observational (registry) study comparing rural and urban adult and pediatric major trauma patients (Injury Severity Score >15) who were injured in a motor vehicle crash (ICD V20-V99) and presented to a level 1 or level 2 trauma centre by EMS by primary or secondary transfer, between April 2011 and March 2013 in a selected province in Canada. Comparisons of the process care times, and patient disposition, were made in an inclusive trauma system.Results: 108 cases meet the inclusion criteria with 78 considered rural and 30 urban using published definitions. The median response times were 16.2 minutes for rural (95% CI: 13.2 -19.8) and 7.8 minutes for urban (95% CI: 7.2 - 10.5) with 60% and 61% meeting response targets respectively . A greater proportion of urban patients are taken initially to level 3-5 centers and require secondary transfer (45% urban vs 24% rural p=<0.01). Median times intervals to surgical care were double for the urban patients (14 rural vs 32 hrs urban p=<0.01).Conclusion: The majority of serious road traffic collisions occur in rural areas. Although rural patients wait longer for an initial EMS response, more rural patients are taken directly to a level 1 or 2 trauma center. Unexpectedly then rural patients have much shorter times to surgical care. The benefits of an inclusive trauma system should be weighed against the benefits of bypass processes in urban environments where the nearest Emergency Department is not a Level 1 or 2 Trauma Center.